Interleukin 2 inhibits in vitro growth of human T cell lines carrying retrovirus (The Rockefeller University Press, 1985)
Four human T cell lines, TL-Mor, TL-Su, TL-TerI, and TL-OmI, carrying human T cell leukemia virus (HTLV), were established previously. TL- Mor, TL-Su, and TL-TerI were derived from interleukin 2 (IL-2)- dependent parental cell lines cloned from peripheral blood leukocytes (PBL) of three healthy HTLV carriers, while TL-OmI was directly established from PBL of a patient with adult T cell leukemia. These four TL cell lines grow autonomously without IL-2. When they were cultured in the presence of IL-2, their growth was inhibited after a few days. This growth inhibition depended on the dose of IL-2, and the effective dose significantly promoted growth of their parental IL-2- dependent cell lines. The growth inhibition is demonstrated to be due to specific binding of IL-2 to receptors on the TL cells.